The process of development of professional and cognitive activity of students - Yuldasheva Malohat Erkinovna. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article analyzes the theoretical foundations of the development of professional and cognitive activity of students. Feedback is made on the need to develop professional cognitive activity of students of future creative and active specialists.